AB0856 A PLACEBO-CONTROLLED, DOUBLE-BLIND, RANDOMIZED, TRIAL OF AMZ001 – A NOVEL DICLOFENAC SODIUM 3.06% GEL - FOR THE TREATMENT OF KNEE OSTEOARTHRITIS SYMPTOMS. (2nd June 2020) - Bihlet, A.; Byrjalsen, I.; Nielsen, H. B.; Andersen, J.; Delpy, L.; Derne, C.; Carrara, D.
Abstract : Background: Development of improved topical treatments of painful joints is warranted. A novel diclofenac sodium gel formulation, AMZ001, has been developed with the purpose of improving 1) The onset and duration of pain relief, and 2) The ease of use by reducing the required daily frequency of gel application. Previous trials in human subjects have confirmed improved permeability of a reduced volume of AMZ001 gel as compared to approved diclofenac topical products with a comparable safety and tolerability profile, supporting trials to evaluate the efficacy and safety of AMZ001 in painful joint conditions. Objectives: The current abstract reports the main results of a randomized trial of AMZ001 once or twice daily application versus placebo in symptomatic knee osteoarthritis. Methods: The trial was a placebo-controlled, parallel group, double-blind, randomized trial to evaluate the efficacy and safety of AMZ001 or placebo in subjects with knee osteoarthritis. The main inclusion criteria were Kellgren-Lawrence radiographic severity of 1-3, and pain ≥40 and ≤90 out of 100 using the WOMAC pain subscale (5 questions) at the time of screening. The subjects were randomized to apply AMZ001 gel once (QD) or twice (BID) daily or placebo twice daily per OA knee for a period of 28 days, or to apply Voltaren® Gel 1 % four times daily (QID) in a single-blind fashion for exploratory comparison. The primary endpoint was change from baseline at week 4 in WOMAC pain (5 questions). The main secondary endpoints included WOMAC subscales, Patient Global Assessment (PGA) and quality of life using the EQ-5D. In addition to the main analysis, a post-hoc subgroup analysis of subjects meeting the pain criterion at both screening and baseline was performed. Results: A total of 444 subjects were randomized. The main baseline characteristics were well balanced between treatment groups. AMZ001 QD and BID led to statistically significant reductions in pain compared to baseline with an estimated difference (95% CI) normalized to 0-100 at week 4 of -27.33 (-30.50, -24.17), and -26.49 (-29.60, -23.38), respectively. Reduction in pain at week 4 was statistically significantly superior to placebo for AMZ001 QD (p=0.04), and borderline significant for AMZ001 BID (p<0.10) as shown in Figure 1 . Both AMZ001 QD and BID led to statistically significant improvements in PGA at week 4 compared to placebo (p<0.05 for both), and AMZ001 BID led to significantly improved quality of life (p<0.05) compared to placebo. There were no statistically significant differences between AMZ001 QD or BID in any of the endpoints. In the post-hoc analysis of subjects meeting the pain criterion at both screening and baseline the differentiation to placebo was strengthened for all efficacy endpoints, as shown in Figure 2 . While the study design and differences in sample sizes does not allow formal comparisons between the double- and single blinded groups, the exploratory comparator, Voltaren QID, did not reach statistically significant differences to placebo or AMZ001 in any of the endpoints, in neither the ITT nor the subgroup analyses. The safety and tolerability of AMZ001 was favorable, as the frequency of AEs leading to discontinuation of treatment was similarly low (ranging between 2.8 % to 6.6 %) between AMZ001 once or twice daily and placebo or Voltaren Gel 1%. The most common treatment-emergent AEs were application site dryness, and application site erythema. No serious adverse events were reported during the trial. Conclusion: AMZ001, a novel topical diclofenac formulation, either once or twice daily was efficacious in the treatment of knee OA pain with a good tolerability and safety profile, suggesting AMZ001 may be a promising alternative to existing pain-relieving treatments in knee OA. References: NA Disclosure of Interests: Asger Bihlet Shareholder of: Nordic Bioscience, Consultant of: Amzell BV, Medivir AB, Xintela AB, Merck KGaA, Employee of: Nordic Bioscience, Inger Byrjalsen Employee of: Nordic Bioscience, Henning Bay Nielsen: None declared, Jeppe Andersen Shareholder of: Minor shareholder of Nordic Bioscience, Consultant of: Medivir AB, Xintela AB, Employee of: Nordic Bioscience, Laetitia Delpy Employee of: Amzell BV, Caroline Derne Employee of: Amzell BV, Dario Carrara Employee of: Amzell BV